ISLAM DAN MARXISME DARI PERSPEKTIF ALI SHARIATI - amir, ahmad nabil; Rahman, Tasnim Abdul (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
The paper aims to discuss the primary ideas and empirical experience of Ali Shariati and his intellectual background as the leading exponent and catalyst of the revolutionary Iranian revolution in 1979 and the shaping of its socio-political landscape. It focuses on his works and critique of the underlying philosophy of Marxism and his rejection of its ideology based on Islamic parameters and its spiritual and metaphysical worldview. The study is qualitative in nature conducted based on literature review, by way of conceptual and historical approaches to interpret and analyze the data. The finding showed that Shariati had formulated a coherence discussion of the Islamic spiritual and mystical construct and its metaphysical bases that contrasted with capitalist perspective and tendency and misleading ideology of atheism, communism, materialism and Marxism. It explained his rigorous argument and dialectical artistry in illuminating the moral and socio-religious ideal of Islam and its universal humanistic framework and liberating theology which contrasted with the anti-religion and soulless ideology and fallacies of Marxism and its fundamental bankruptcy in moral and practical term